2015
DOI: 10.1371/journal.pone.0116188
|View full text |Cite
|
Sign up to set email alerts
|

Telecare for Diabetes, CHF or COPD: Effect on Quality of Life, Hospital Use and Costs. A Randomised Controlled Trial and Qualitative Evaluation

Abstract: ObjectivesTo assess the effect of telecare on health related quality of life, self-care, hospital use, costs and the experiences of patients, informal carers and health care professionals.MethodsPatients were randomly assigned either to usual care or to additionally entering their data into a commercially-available electronic device that uploaded data once a day to a nurse-led monitoring station. Patients had congestive heart failure (Site A), chronic obstructive pulmonary disease (Site B), or any long-term co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
100
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(103 citation statements)
references
References 32 publications
(26 reference statements)
2
100
0
Order By: Relevance
“…4,12,16,2022 Also, five out of 20 articles (25%) reported a decrease in the length of hospital stay due to longer follow-up periods, and this accounted for 8% of all occurrences of attributes. 4,8,9,18,19 …”
Section: Resultsmentioning
confidence: 99%
“…4,12,16,2022 Also, five out of 20 articles (25%) reported a decrease in the length of hospital stay due to longer follow-up periods, and this accounted for 8% of all occurrences of attributes. 4,8,9,18,19 …”
Section: Resultsmentioning
confidence: 99%
“…[25,42] Introducing a POC device into practice is a complex intervention and as such poses major challenges to the RCT design as it is largely determined by human agency. [43] It could be argued that this multifaceted intervention may have been better if we provided more training and support to embed such a tool into practice workflow.…”
Section: Discussionmentioning
confidence: 99%
“…However, qualitative studies report that patients are mostly positive about their experiences, reporting that they felt safer and that they had learned more about their condition, and staff felt that the improved knowledge could be a useful long-term benefit. 81 Earlier qualitative work had also suggested that interacting with a telehealth intervention and receiving feedback from the health professional can increase satisfaction in relation to factors such as continuity of care, understanding of symptom variability and encouragement of self-management behaviour. 82 While participants were mostly positive about their role in telemonitoring, several were glad to hand their devices back at the end of this short (3-6 month) study, stating that they were getting bored using it everyday.…”
Section: Technology and Copdmentioning
confidence: 99%